The existential realities of dancing - Sheets-Johnstone, Maxine (Frontiers in Cognition, 2024)
Can we again learn about ourselves and our surrounding world by way of dance as we are ageing and thereby promote our own health? This article documents facts of life showing that “the elderly” do not have to learn to be cognitive of their movement, their affective dispositions, or their surrounding world; they have been experientially cognitive of all by way of tactility, kinesthesia, and affectivity from the start. Present-day cognitive neuroscience is deficient in recognizing these experiential realities, concentrating and theorizing as it does on the neuroplasticity of the brain. Research studies of brain and behavior, in contrast, demonstrate that coordination dynamics are the defining feature of both: neurological and kinesthetic coordination dynamics are central to corporeal concepts, to recognition of if/then relationships, and to thinking in movement. In effect, the brain is part of a whole-body nervous system. The article proceeds to show that the qualitative dynamics of movement that subtend coordination dynamics are basic not just to everyday movement but to dancing--to kinesthetically experienced movement and to being a mindful body. When Merce Cunningham writes that dance gives you that “single fleeting moment when you feel alive” and is not for “unsteady souls” and when English writer D. H. Lawrence writes that “We ought to dance with rapture that we are alive, and in the flesh, and part of the living incarnate cosmos,” their words are an incentive to those who are ageing to awaken tactilely, kinesthetically, and affectively to the existential realities of dance.